2016
DOI: 10.1016/j.jcps.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Compensatory Consumer Behavior Model: How self‐discrepancies drive consumer behavior

Abstract: Consumer goods and services have psychological value that can equal or exceed their functional value. A burgeoning literature demonstrates that one source of value emerges from the capacity for products to serve as a psychological salve that reduces various forms of distress across numerous domains. This review systematically organizes and integrates the literature on the use of consumer behavior as a means to regulate self-discrepancies, or the incongruities between how one currently perceives oneself and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
455
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(486 citation statements)
references
References 119 publications
(171 reference statements)
22
455
1
8
Order By: Relevance
“…The present research also adds to a growing body of compensatory consumption research which demonstrates that social motivations guide consumption decisions (Mandel, Rucker, Levav, & Galinsky, 2016; Rucker & Galinsky, 2008). For example, Dubois, Rucker, and Galinsky (2012) found that feeling powerless motivates consumers to prefer supersized food and drinks, because larger options are status‐signaling and can fulfill the need for status.…”
Section: Theoretical Background and Current Studiesmentioning
confidence: 87%
See 2 more Smart Citations
“…The present research also adds to a growing body of compensatory consumption research which demonstrates that social motivations guide consumption decisions (Mandel, Rucker, Levav, & Galinsky, 2016; Rucker & Galinsky, 2008). For example, Dubois, Rucker, and Galinsky (2012) found that feeling powerless motivates consumers to prefer supersized food and drinks, because larger options are status‐signaling and can fulfill the need for status.…”
Section: Theoretical Background and Current Studiesmentioning
confidence: 87%
“…In the current research, we examine how consumers' motives for social affiliation influence their responses to anthropomorphized brands. As discussed earlier, experiencing social exclusion increases individuals' motivation to pursue social reconnection and increases their sensitivity to cues that imply opportunities for acquiring new social relationships (DeWall et al, 2009; Williams et al, 2000). In a consumption context, brands presented in an anthropomorphized form can potentially become a target with which consumers can build social relationships.…”
Section: Theoretical Background and Current Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review also provides a nomological network for the antecedents and consequences of resource scarcity to support our theory (Gray, ). Finally, we compare the explanatory power of our self‐regulatory model of consumers’ responses to resource scarcity to related theoretical perspectives, such as theories of problem‐ and emotion‐focused coping (Han, Duhachek, & Rucker, ), and theories of compensatory behaviors (Mandel, Rucker, Levav, & Galinsky, ; Proulx & Inzlicht, ).…”
Section: Introductionmentioning
confidence: 99%
“…Possessions play an important role in coping with life transitions and change (Belk, ; Mehta & Belk, ; Noble & Walker, ). Mandel, Rucker, Levav, and Galinsky () theorize five compensatory consumption behaviors in which possessions are used to resolve an incongruity directly, to communicate mastery in the area of self incongruity, to dissociate from a particular identity, to escape or distract from the self‐discrepancy, and/or to reinforce valued aspects of identity in a different domain. Although the first of these five strategies is unlikely to be implemented in domestic violence, the remaining strategies are relevant to this research context.…”
Section: Background To the Researchmentioning
confidence: 99%